Adapting food environment frameworks to recognize a wild-cultivated continuum - Zeitler, Lilly; Downs, Shauna; Powell, Bronwen (Frontiers in Nutrition, 2024)
Food environments, or interfaces between consumers and their food systems, are a useful lens for assessing global dietary change. Growing inclusivity of nature-dependent societies in lower-and middle-income countries is driving recent developments in food environment frameworks. Downs et al. (2020) propose a food environment typology that includes: wild, cultivated, informal and formal market environments, where wild and cultivated are "natural food environments." Drawing from transdisciplinary perspectives, this paper argues that wild and cultivated food environments are not dichotomous, but rather exist across diverse landscapes under varying levels of human management and alteration. The adapted typology is applied to a case study of Indigenous Pgaz K'Nyau food environments in San Din Daeng village, Thailand, using the Gallup Poll's Thailand-adapted Diet Quality Questionnaire with additional food source questions. Wild-cultivated food environments, as classified by local participants, were the source of more food items than any other type of food environment (37% of reported food items). The case of Indigenous Pgaz K'Nyau food environments in San Din Daeng village demonstrates the importance of understanding natural food environments along a continuum from wild to cultivated.